Alternative and facile production pathway towards obtaining high surface area PtCo/C intermetallic catalysts for improved PEM fuel cell performance. Issue 7 (6th February 2023) - Heizmann, Philipp A.; Nguyen, Hien; von Holst, Miriam; Fischbach, Andreas; Kostelec, Mitja; Gonzalez Lopez, Francisco Javier; Bele, Marjan; Pavko, Luka; Đukić, Tina; Šala, Martin; Ruiz-Zepeda, Francisco; Klose, Carolin; et al.
Abstract : A novel PtCo/C based PEMFC electrocatalyst was investigated in real fuel cells under application-relevant conditions. The corresponding MEAs show superior performance compared to reference materials due to more suitable nanoparticle sizes. Abstract : The design of catalysts with stable and finely dispersed platinum or platinum alloy nanoparticles on the carbon support is key in controlling the performance of proton exchange membrane (PEM) fuel cells. In the present work, an intermetallic PtCo/C catalyst is synthesized via double-passivation galvanic displacement. TEM and XRD confirm a significantly narrowed particle size distribution for the catalyst particles compared to commercial benchmark catalysts (Umicore PtCo/C). Only about 10% of the mass fraction of PtCo particles show a diameter larger than 8 nm, whereas this is up to or even more than 35% for the reference systems. This directly results in a considerable increase in electrochemically active surface area (96 m 2 g −1 vs. >70 m 2 g −1 ), which confirms the more efficient usage of precious catalyst metal in the novel catalyst. Single-cell tests validate this finding by improved PEM fuel cell performance. Reducing the cathode catalyst loading from 0.4 mg cm −2 to 0.25 mg cm −2 resulted in a power density drop at an application-relevant 0.7 V of only 4% for the novel catalyst, compared to the 10% and 20% for the commercial benchmarks reference catalysts.